Analisis Kebutuhan Inovasi Teknologi terhadap Peningkatan Kinerja Pegawai Kementerian Desa, Pembangunan Daerah Tertinggal dan Transmigrasi Republik Indonesia - Sugiman, Iman; Luthfie, Muchtar; Taufikkurohman, Rizal (Jurnal Ilmu Manajemen, 2020)
This study aims to analyze the needs associated with technological innovation to improve employee performance at the Center for Community Training Development of the Ministry of Villages, PDT, and Transmigration of the Republic of Indonesia. The research approach used is qualitative research, adopting a needs analysis model developed by Witkins and Altschul. The study used data collection techniques and tools through questionnaires, interview guidelines, and supporting documents. This research collaborates with the head of the division at level one, a staff member from the administration division, and the data management and information system program. Various recommendations for solutions that can be applied instructional are applying the application of technological innovation, analyzing the application of technological innovation, evaluating technological innovation, developing technological innovation models.